A Research Agenda for Environmental Law - van Zeben, Josephine; Hilson, Chris (Edward Elgar Publishing, 2025)
This is an open access title available under the terms of a CC BY-NC-ND 4.0 License. It is free to read, download and share on Elgaronline.com. As environmental realities become ever more urgent and severe, it is crucial to reflect on the potential solutions that the law can offer. This timely Research Agenda introduces new directions for study and practice, presenting insights into the role of environmental law in securing a sustainable society.